The Effect of Job Satisfaction and Workload on Turnover Intention Moderated by Organizational Commitment - Prastya Adjie Herlambang Laut; Habib Rifki Syahrizal (Journal of Management and Digital Business, 2024)
Purpose – This study aims to test, analyze, and obtain empirical evidence regarding the effect of job satisfaction and workload on turnover intention moderated by organizational commitment at PT Bluebird Raden Inten branch. From the results of the study, it is known that the job satisfaction variable has a positive and insignificant effect on turnover intention, the workload variable has a significant positive effect on turnover intention, the organizational commitment variable does not moderate the relationship between job satisfaction and turnover intention significantly, while the organizational commitment variable does not moderate the relationship between workload and turnover intention significantly. Design/methodology/approach – The study employees quantitative research methods, using primary data collected from a population of 50 employee in PT Bluebird Tbk Raden Inten branch. Data analysis is conducted using Partial Least Square (PLS) software with Moderated Regression Analysis.  Findings – This research is expected to provide information related to turnover intention g and provide benefits in making the right decisions and can be used as a reference for further research Research limitations/implications – This study has several limitations that must be considered when interpreting the results. The sample size is limited to 1 company PT Bluebird Raden Inten branch and the number of respondents who need assistance to fill out the research questionnaire so that it takes longer than the research period.